Manajemen risiko kredit dalam meningkatkan stabilitas bank - Ahla, Hilwiyatul (Maliki Interdisciplinary Journal, 2026)
Credit risk management is a crucial element in maintaining banking sector stability. Credit risk arises when borrowers fail to fulfill their payment obligations according to the terms of the agreement, which can result in an increase in non-performing loans (NPLs). This study aims to explore the contribution of credit risk management to maintaining bank stability by referring to various empirical studies and relevant literature. The approach taken is descriptive qualitative through literature analysis and secondary data processing. The study findings indicate that the systematic implementation of credit risk management, from identification, assessment, monitoring, to risk control, can reduce the NPL ratio to a safe threshold according to regulatory requirements, namely below 5%. Furthermore, a study by (Nugroho, 2025) revealed that the use of technology such as a loan management system (LMS) and strengthening internal control systems can improve the accuracy of credit evaluations while reducing the likelihood of non-performing loans. Furthermore, credit risk is influenced by internal and external factors, including the quality of organizational supervision and the macroeconomic situation. Bank stability will be better maintained if risk management is implemented in an integrated manner with quality leadership, supported by a competent workforce, and the use of appropriate technology. Thus, credit risk management not only functions as a control measure, but also as a vital strategy in maintaining the sustainability of the banking system.